Effect of the Meso/Beta Halogenation in the Photoelectronic Properties and Aromaticity of Expanded Porphyrins - Cardenas-Jiron, G; Pino-Rios, R (Elsevier B.V., 2019)
A systematic analysis of the photoelectronic properties and aromaticity in meso and beta halogenated expanded porphyrins (Sapphyrin and Orangarin), have been carried out by means of Time Dependent Density Functional Theory (TD-DFT) and magnetic criteria of aromaticity. Results indicate that there is a notorious redshift in the Soret-type (Q-type) bands. The electronic absorption of meso-substituted compounds showed a strong redshift in aromatic porphyrins compared to its beta counterpart and can be attributed to the lower energy gap. For antiaromatic derivatives an inverse trend is observed where beta compounds have a greater redshift than meso compounds. Additionally, major redshifts are observed for the Q bands in iodine-derived compounds. Magnetic aromaticity analysis showed that there is a systematic decrease for aromatic derivatives, following a periodical trend (F to I), whereas a decrease in antiaromaticity for orangarin derivatives is found. Finally, correlations have been found between the energy gaps and Q-type bands of the aromatic porphyrins studied. Halogenation strategy for enhancing the properties in aromatic/antiaromatic porphyrins could be useful in the design of chromophores with potential application in dye sensitized solar cells. © 2019 Elsevier B.V.